The hypothesis of the relationship between the current seismic process and the geomagnetic field pulsations - Brodsky, Yu. B.; Gannoshyn, V. P. (Ukrainian Antarctic Journal, 2009)
With respect to the increased frequency of the seismic activity symptoms and their disastrous aftereffects and taking into account the publications devoted to severe earthquakes in the Antarctica (1998), Kaliningrad oblast (2004), China (2008), Kirghizia (2008), South Pakistan (2008) and other places, the paper presents the analysis of the influence of the seismic process on the effects in the circumterrestrial plasma. The authors propose a new hypothesis of the relationship in the lithosphere – geomagnetic field system which is based on the interaction between the moving tectonic plates and the Earth’s magnetic field. Alongside with the seismic process development the linear velocity of the tectonic plate deformation is increasing which results in the change in the shape of the geomagnetic field intensity line, which, though elastic, is trying to take its initial shape. The changes in the shape of the geomagnetic field intensity line bring about the appearance of the oscillation process of the latter (the so-called stationary wave). In the critical moment of time, when the rock reaches its ultimate stress limit, one can observe the discontinuity or the Earth’s crust fault which is accompanied by a rapid increase in the oscillation amplitude of the force geomagnetic line. The paper also presents the results of modelling the pulsations of the geomagnetic field Z-component, the above testifying to a direct relationship and the disturbance of the Earth’s magnetic field. The estimates obtained are nicely coordinated with the results of geomagnetic field pulsation measurements which were carried out on the Academician Vernadsky station before the severe crust earthquake in the Antarctics on the 25 of March 1998 (Bakhmutov, Sedova, Mozgovaya, 2003).